Morphophonemic Analysis of the Novel Ingkar by Boy Candra: Phoneme Changes, Phoneme Additions, and Phoneme Deletions - Duwi Andinis; Wahyu Widayati; Simanjuntak, Nensy Megawati (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Along with the times and advances in technology, language is also experiencing changes which result in the formation of new vocabulary and new variations of morphemes. To understand the process of change, researchers are encouraged to conduct research in the field of morphophonemics. This study examines the morphophonemic processes in Boy Candra's novel